Extreme flooding increases poaching mortality in the southernmost stronghold of the endangered marsh deer - Pereira, Javier Adolfo; Varela, Diego; Thompson, Jeffrey J.; Lartigau, Bernardo V.; Fracassi, Natalia; Kittlein, Marcelo J. (Sociedad Argentina para el Estudio de los Mamíferos (SAREM), 2023)
Extreme stochastic perturbations can affect population dynamics, but quantitative assessments are scarce for threatened species. The 2015-2016 El Niño-Southern Oscillation (ENSO) caused extreme flooding in the Delta of the Paraná River in Argentina where the southernmost population of the regionally endangered marsh deer (Blastocerus dichotomus) occurs. Using field surveys and data from informants, we studied the impact of this flood on the mortality, distribution, and abundance of this marsh deer population in an area of 1 236 km2. The occurrence of this extreme flood significantly increased marsh deer mortality. One hundred forty-two marsh deer deaths were recorded over the seven-month flood duration, with poaching accounting for 86.6% of deaths. Mortality of marsh deer was significantly higher near urban areas, embankments, and dirt roads, while mortality from poaching was higher in plantations and permanently inundated lands. Two areas of high spatial clustering of poaching mortality were detected, encompassing plantations with easy access or in proximity to urban areas, while embankments appeared to act as attractive population sinks. Flood-related mortality significantly decreased the occurrence of the species in the study area after the flood, but changes in relative abundance between periods were heterogeneous across the landscape, probably because of local migrations. Since climate change is expected to increase the global frequency and magnitude of extreme flood events, our study provides valuable information for mitigating the negative synergistic effects of extreme flooding on marsh deer, as well as for global wildlife populations subjected to periodic extreme floods.